The Influence of Bi'ah Lughawiyyah on Arabic Language Acquisition: A Case Study of Firtalia Members from the Perspectives of Social Cognitive Theory and Psycholinguistics - Eldho Pranthara; Abdul Kirom (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2025)
Arabic language acquisition is influenced by linguistic, cognitive, and psychological factors, and is supported by a structured and conducive language environment (bi’ah lughawiyyah) within the Firtalia community. This study aims to examine in greater depth how a systematically and sustainably managed language environment influences the language competence and psychological readiness of its members. This study employs a qualitative case study methodology, with data collected through in-depth interviews, participant observation, and document analysis to capture authentic, contextual, and dynamic language practices. The findings indicate that structured daily Arabic language interactions, peer modeling, and consistent routine practices effectively enhance speaking and listening competencies, while significantly reducing language anxiety and boosting learners’ self-efficacy. This enables learners to communicate with greater confidence and engagement, producing more complex utterances. These findings indicate that Arabic language acquisition at Firtalia is a socially mediated, cognitively reinforced, and psychologically supported process, thereby underscoring the importance of integrating structured environmental exposure, social support, and motivation in language learning. Keywords: Bi'ah lughawiyyah, Arabic language acquisition, self-efficacy